THE DEVELOPMENT OF STRATEGY OF INDONESIAN NAVAL REPAIRMENT AND MAINTENANCE FACILITY (FASHARKAN) TO SUPPORT THE READINESS OF BATTLESHIPS IN FIRST FLEET COMMAND BY USING TOWS METHOD (CASE STUDY FASHARKAN JAKARTA) - Kuncoro Kuncoro; Budisantoso Wirjodirdjo; Okol Sri Suharyo; As'ad Aris Mustofa (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Repair and Maintenance facility Jakarta is supporting facility component of Indonesian Naval Fleet which has duties to maintain and repair the ships that location is very strategics in Naval Base I. This is as KRI berth and technical condition preparation before doing the operation. The purpose of this research is to determine alternative strategy and roadmap for developing Fasharkan Jakarta with using TOWS analysis (Treaths Opportunities Weaknesses Strength) and ISM (Interpretative Structural Modeling). According to result of TOWS matrix analysis, SO strategy is consisting of eight strategic, four strategic for ST, nine strategic for WO, and four strategic for WT. Based on Weighting by using EFAS and IFAS matrix, WO strategy is as the choosen strategy, as the result WO strategy is become the first alternative. According to the elements clarification results for WO strategy, it gets five levels hierarchy. In this hyrarcy structure can be known that WO8 and WO9 sub strategies are in the level five position, then WO7 sub strategy in the level four strategy. Besides, in the level III is consist of WO5, in the level II is sub strategy WO1, WO3, WO6 and in the level I there are WO2 and WO4 sub strategies. Keywords: Repair and Maintenance Facility Jakarta, Developing Strategic, TOWS and ISM.